Pengaruh Manajemen Reproduksi terhadap Tingkat Keberhasilan Kebuntingan pada Sapi Bali - Andi Pratama (Journal of Animal Husbandry, 2025)
The reproductive performance of Bali cattle plays a crucial role in supporting livestock productivity and the sustainability of local cattle breeding programs. Reproductive management, including estrus detection, artificial insemination (AI), and nutritional support, significantly influences pregnancy success rates. This study aimed to evaluate the impact of reproductive management practices on pregnancy success in Bali cattle. A field survey and direct observation were conducted on 120 Bali cows in Central Lombok, Indonesia, from March to August 2024. Data collection included reproductive records, AI service efficiency, body condition score (BCS), and farmer management practices. Statistical analysis was performed using logistic regression to identify factors affecting pregnancy success. The results showed that timely estrus detection, AI accuracy, and adequate nutrition were the most significant determinants of conception rate (p < 0.05). Bali cattle with good BCS (≥3.0) and proper estrus detection had a higher pregnancy success rate (78%) compared to those with poor management (42%). The study concludes that improving reproductive management, particularly in estrus detection training for farmers and nutritional supplementation, enhances the reproductive efficiency of Bali cattle. These findings provide valuable insights for policymakers, livestock extension workers, and farmers in optimizing reproductive strategies for sustainable cattle production in tropical environments.